Perancangan dan Implementasi Fitur Pencairan Cepat pada Website Akademik Fakultas - Arifin, Muhammad Khoirul; Sari, Rafika (Journal of Informatic and Information Security, 2024)
In the digital era, ease of information access plays a crucial role in the effectiveness of an academic website. The Faculty of Psychology at Universitas Bhayangkara Jakarta Raya faces challenges in providing quick and efficient access to information for users. This internship report aims to design and implement a quick search feature on the faculty’s website to enhance user experience. The methods used include observation, interviews, and literature studies to understand user needs and technical system development. The implementation of a JSON-based search feature allows for faster and more accurate information retrieval. Testing results show that this feature improves search efficiency by up to 90%, with high user satisfaction based on conducted surveys. Future development may include integration with a more complex database system and the addition of filtering features to improve search result relevance